Periodontal parameters following orthodontic treatment in patients with aggressive periodontitis: A before-after clinical study - Afshin Khorsand; Mojgan Paknejad; Siamak Yaghobee; Amir Alireza Rasouli Ghahroudi; Hourieh Bashizadefakhar; Masoomeh Khatami; Mohsen Shirazi5 (Wolters Kluwer Medknow Publications, 2013)
Background: The success of combined periodontal and orthodontic approach in the treatment of aggressive periodontitis patients with the pathologic extruded anterior teeth is a main concern and stability of the treatment results is an important factor to evaluate the treatment. The present study investigated the periodontal parameters at the end of the orthodontic treatment in patients with the aggressive periodontitis. Materials and Methods: Eight patients with an aggressive periodontal disease, extruded maxillary incisors, infrabony defects and probing depth of ≥5 mm were enrolled in this clinical trial (before, after). After periodontal therapy, orthodontic treatment was carried out for intrusion and alignment of teeth. Plaque index (PI), probing pocket depth (PPD), distance between incisal edge and interdental papilla, root length (RL), and defect dimensions (depth and width) were examined at the end of treatment and three as well as 6 months afterward. The data were subjected to repeated measure ANOVA test. P < 0.05 was considered as significant. Results: There was statistically significant decrease in PPD, PI, and depth of the defects during T0, T3 and T6 (P < 0.05). No significant differences were observed in the RL and distance between incisal edge and interdental papilla (P = 0.95). Furthermore, width of the defects demonstrated significant decrease up to T3 (P = 0.042) while no significant changes from 3 months to 6 months were noted (P = 0.59). Conclusion: The results showed that combined periodontal and orthodontic approach would be a successful treatment with acceptable stability in the case of regular follow-up visits and controlled oral hygiene habits.